The Oregon Trail - Uschan, Michael V., 1948- (World Almanac Library, 2004)
Examines the famous westward route of American settlement during the 1800s, including everyday life on the trail, what it took to make the journey successfully, and what happened to unsuccessful attempts to reach the Oregon territory.